2017
DOI: 10.1007/8904_2017_42
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in White Matter Fractional Anisotropy in Adult-Onset Niemann-Pick Disease Type C Patients Treated with Miglustat

Abstract: Niemann-Pick disease type C (NPC) is a rare neurometabolic disorder resulting in impaired intracellular lipid trafficking. The only disease-modifying treatment currently available is miglustat, an iminosugar that inhibits the accumulation of lipid metabolites in neurons and other cells. This longitudinal diffusion tensor imaging (DTI) study examined how the rate of white matter change differed between treated and non-treated adult-onset NPC patient groups. Nine adult-onset NPC patients (seven undergoing treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…NPC1 −/− mice present accumulation of unesterified cholesterol in different tissues, abnormalities in lysosomal enzyme levels, increased activity of hepatic enzymes and decreased levels of triacylglycerides ( Pentchev et al., 1980 ; Amigo et al., 2002 ; Beltroy et al., 2005 , 2007 ; Kulinski and Vance, 2007 ). At present there is no cure for Niemann-Pick disease, and the only available treatment, Miglustat, can alleviate symptoms but does not cure the disease (( Wraith et al., 2010 ; Bowman et al., 2015 ; Sedel et al., 2016 ; Bowman et al., 2018 ), for review see ( Lyseng-Williamson, 2014 )).…”
Section: Introductionmentioning
confidence: 99%
“…NPC1 −/− mice present accumulation of unesterified cholesterol in different tissues, abnormalities in lysosomal enzyme levels, increased activity of hepatic enzymes and decreased levels of triacylglycerides ( Pentchev et al., 1980 ; Amigo et al., 2002 ; Beltroy et al., 2005 , 2007 ; Kulinski and Vance, 2007 ). At present there is no cure for Niemann-Pick disease, and the only available treatment, Miglustat, can alleviate symptoms but does not cure the disease (( Wraith et al., 2010 ; Bowman et al., 2015 ; Sedel et al., 2016 ; Bowman et al., 2018 ), for review see ( Lyseng-Williamson, 2014 )).…”
Section: Introductionmentioning
confidence: 99%
“…Bowman et al 14,15 examined longitudinally a collection of nine adult patients in comparison to a healthy person. The MR follow-up showed that the untreated patients had less thalamic and cerebellar gray and white matter volume over time compared with both controls and treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutically, Miglustat (Zavesca) is a targeted treatment for neurological deterioration in NPC [9] and we hope find a therapeutic alternative for systemic signs.…”
Section: Discussionmentioning
confidence: 99%